Relationship of Conformity with Adolescent Impulsion Buying Behavior on Fashion Products in Marketplace with Self-Control as a Moderating Variable - Egi Vizya Adri; Dedi Setiawan; Okuard Methindo (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
The aim of this study is to determine the effect of conformity on adolescent impulsive buying behavior on fashion products in the marketplace moderated by self-control. The research method used in this research is quantitative. The data collection used in this research is by sharing the questionnaire in the form of Google Form starts from July to September. The researchers use non-probability sampling method with voluntary response sampling. Respondents in this study are 150 teenagers. The data analysis technique used in this research is multiple linear regression analysis. Based on the results of data analysis carried out, it is found that there is a significant relationship between conformity to adolescent impulsive buying behavior. Furthermore, the self-control variable as a moderating variable also has a significant effect on the independent and dependent variables in this study. The results of the study found that the conformity variable (X) simultaneously affected the impulsive buying variable (Y) by 73.1%, while 26.9% is influenced by other variables outside the regression equation or variables that are not examined. Other than that, the self-control as the moderation variable can moderate the effect between conformity and impulse buying in adolescents. For further research, there needs other variables that can be conducted to know what affects impulse buying with conducting to other types of society other than an adolescent.